Corynebacterium striatum‐Associated Pyogenic Osteomyelitis With Direct Extension From Postoperative Empyema - Shinnosuke Fukushima; Kazuhiro Noma; Hideharu Hagiya (Respirology Case Reports)
ABSTRACT Corynebacterium striatum can cause postoperative empyema. C. striatum‐associated empyema may be associated with osteomyelitis. Rifampicin is a viable therapeutic option for C. striatum infection.